Pengaruh Penempatan Kerja Dan Pengalaman Kerja Terhadap Kinerja Karyawan Pada PT Indonesia Trans Network - Sintiya Permata Sari; Iskandar Ali Alam (Universitas 17 Agustus 1945 Semarang, 2023)
In this investigation, we'll find out whether work placement and work experience affect employee performance at PT. Indonesia Trans Network. In this study employing analytical techniques, namely where the subjects of this study amounted to 31 employees of PT. Indonesia Trans Network. The sample is census sampling or saturated sampling, namely the whole populace is employed as a study example. The method of data analysis employs multiple linear regression using SPSS version 26 software. The results of the research by testing the hypothesis show that work placement and employment history have a favorable and significant impact on employees' performance at PT. Indonesia Trans Network. The proportion of the two variables on employee performance is 57%, while the remaining 43% is influenced by other factors in the regression model.